Study of Waste Generations and Potential Implementation of Community-Based Waste Management in Residential Area - Cut Febie Idilia; Meti Ekayani; Nuva Nuva (Department of Geography Education, University of Jember, 2023)
Bogor is one of the cities in Indonesia with a dense population and is experiencing population growth every year. Like other city problems, waste is also a problem in Bogor City. Waste generation in cities like Bogor City has been continued to increase since 2005. Even though the Bogor City Government has socialized with changes in waste management with a new paradigm, those living in residential areas are still using the old paradigm principle which is collect-transport-throw (end of a pipe). Therefore, a study was conducted to determine the waste generated and the perception and role of community participation in managing waste, especially household waste in residential areas. In this study, data collection was carried out in one of the housing areas in Bogor City, namely the Pakuan Regency. The collection of daily waste data to measure waste generation and composition is carried out based on the Indonesian National Standard 19-3964-1994 method. This data analysis technique uses a qualitative descriptive analysis with respondents differentiated on the basis of type of house and the number of occupants. This research produces data on waste generation for small, medium, and large house types 286,12 kg/houses/year, 366,57 tons/houses/year, and 523,67 kg/houses//year respectively. The result showed that the total of household waste, the level of participation and the household’s willingness to pay for TPS 3R plan made it possible to implement the TPS 3R program in this residential. Operational cost for TPS 3R can be covered from the retribution annual revenue.